Autoimmune Bullous Disease Quality of Life (ABQoL) questionnaire: Validation of the translated Persian version in pemphigus vulgaris - Amir Teimourpour, PhD; Kowsar Hedayat, MD; Fereshteh Salarvand, MD; Narges Ghandi, MD; Maryam Ghiasi, MD; Hamidreza Mahmoudi, MD; Kamran Balighi, MD; Roja Toosi, MD, MPH; Farnam Mohebi, MD, MPH; Ali Nili, MD; Maryam Daneshpazhooh, MD; Dedee F. Murrell, MA, BMBCh, MD, FACD; et al. (Wolters Kluwer, 2020)
Background: Autoimmune bullous diseases are a group of rare, chronic, blistering diseases, with pemphigus vulgaris (PV) being the most common type in Iran. Skin and mucosal involvement and therapy may have a dismal impact on the quality of life of affected patients. Objective: We aimed to assess the validity and reliability of the Farsi (Persian) version of the Autoimmune Bullous Quality of Life (ABQoL) index in Iranian patients with PV. Methods: Forward and backward translation procedures were used to prepare the Persian version of the ABQoL questionnaire. A total of 180 patients were asked to complete the questionnaires, and 24 cases repeated the test after 2 weeks. For validity and reliability, an exploratory factor analysis was performed along with a parallel analysis to determine the number of factors. The multi-trait, multi-method matrix assessed convergent and discriminant validity. To evaluate internal reliability and reliability over time, Cronbach's alpha and intraclass correlation coefficients were reported. Results: Two factors explained a total variance of 54.9% in the data. The first and second factors comprised questions 1-3, 5, 7, 9, and 12-17 (symptoms-social) and questions 4, 6, 8, 10, and 11 (mucosal-psychological), respectively. The internal reliability of the Persian version of the ABQoL index was also acceptable, with a Cronbach's alpha of .855 for total items, .918 for the first factor, and .6 for the second factor. Our results suggest an acceptable convergent and discriminant validity of the Persian version of the ABQoL questionnaire. Conclusion: The Persian version of ABQoL index is a valid and reliable tool to monitor quality of life in patients with PV. Further studies are needed to assess the sensitivity of this instrument to changes in different disease activity and correlation with more general tools for the measurement of quality of life.